2016
DOI: 10.1021/acs.jctc.5b01163
|View full text |Cite
|
Sign up to set email alerts
|

Troubles in the Systematic Prediction of Transition Metal Thermochemistry with Contemporary Out-of-the-Box Methods

Abstract: The recently developed DLPNO-CCSD(T) method and seven popular DFT functionals (B3LYP, M06, M06L, PBE, PBE0, TPSS, and TPSSh) with and without an empirical dispersion term have been tested to reproduce 111 gas phase reaction enthalpies involving 11 different transition metals. Our calculations, corrected for both relativistic effects and basis set incompleteness, indicate that most of the methods applied with default settings perform with acceptable accuracy on average. Nevertheless, our calculations also evide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
47
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(52 citation statements)
references
References 211 publications
5
47
0
Order By: Relevance
“…43 Subsequent studies indicated that the documented failure can be related to insufficiently large basis sets. 44,45 Indeed, we have recently shown that many reaction enthalpies involving transition metals were not affected by the frozen core approach 18,46 We do not exclude that in many cases the surprisingly good performance of the FC approach might result from the lucky cancellation of errors from neglecting core and core-valence correlation in both reactants and products. However, few reactions turned out to be very sensitive to the frozen core settings, leading to errors of 30-40 kcal mol À1 when the default FC settings were used, for example reactions of ZrF 4 with Cl 2 , Br 2 or I 2 .…”
Section: Introductionmentioning
confidence: 95%
“…43 Subsequent studies indicated that the documented failure can be related to insufficiently large basis sets. 44,45 Indeed, we have recently shown that many reaction enthalpies involving transition metals were not affected by the frozen core approach 18,46 We do not exclude that in many cases the surprisingly good performance of the FC approach might result from the lucky cancellation of errors from neglecting core and core-valence correlation in both reactants and products. However, few reactions turned out to be very sensitive to the frozen core settings, leading to errors of 30-40 kcal mol À1 when the default FC settings were used, for example reactions of ZrF 4 with Cl 2 , Br 2 or I 2 .…”
Section: Introductionmentioning
confidence: 95%
“…they represent a balanced data set for which the performance can be divided into system type. Previous similar studies [11][12][13][29][30][31] should be considered in this context. The main novelty of our study is the use of a balanced dataset studied with a wide range of Theory and Computation 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 6 modern density functionals of various design types.…”
mentioning
confidence: 97%
“…[23] This method was shown to provide results of canonical coupled cluster quality. [24][25][26][27][28][29][30] All the calculations were performed for gas phase.…”
Section: Computational Detailsmentioning
confidence: 99%
“…Thus, dodecahedrane cage seems to be the best fit for fluorine atom. Another try to improve the structure was changing cyano groups to CF 3 ones, but that quickly lead to 20 9.766 −11.768 F@C 24 (CN) 24 9.502 −11.482 F@C 28 (CN) 28 9.484 −11.455 overcrowding of fluorine atoms, preventing the proper delocalization of negative charge. Looking at carborane cages, we noticed that the cage CB 11 of C 5v symmetry, decorated with 12 CF 3 groups ( Fig.…”
Section: Possible Improvementsmentioning
confidence: 99%
See 1 more Smart Citation